Modelo ProLab: Fintech Yachay Pacha, alternativa para reducir la deserción estudiantil en universidades privadas de Lima Metropolitana - Chacón Mayo, David Sebastián (2025)
University dropout rates in private universities in Metropolitan Lima currently reach 14% (Ministerio de Educación [Minedu], 2023a), which translates into approximately 69,000 students who abandon their studies annually, which impacts individual academic development, and therefore, economic and social impacts at the national level. The lack of financial resources to cover academic expenses is a main cause of this dropout, which limits the development of human capital and, consequently, the capacities of graduates to effectively contribute to the country's economic growth. According to the Organization for Economic Cooperation and Development (OECD 2023), each additional year of education can increase income by 8-10%, which highlights the potential loss in gross domestic product (GDP) associated with a dropout rate of 14%. From a social perspective, dropout particularly affects 68.9% of students from socioeconomic levels (SES) B and C, according to Encuesta Nacional de Hogares (Enaho, 2022) (as cited in Asociación Peruana de Empresas de Inteligencia de Mercados [Apeim, 2024]). This reduces their employment opportunities. The financing solutions available so far, such as the loans offered by Lumni and the alternatives of the National Scholarship and Educational Credit Program (Pronabec), present significant limitations in terms of accessibility and flexibility, especially affecting low-income students. The strict requirements to access loans limit the ability of many young people between 20 and 25 years of age to complete their higher education. The financial evaluation of the proposed solutions indicates a positive economic impact, a net present value (NPV) of S/4'105,152 as well as an internal rate of return (IRR) of 24%. The social NPV of S/4’529,673 indicates a significant impact, being 6 times greater than the financial NPV. With a social discount rate of 8% established by Ministerio de Economía y Finanzas (MEF), which reflects its high social profitability. Yachay Pacha implements a more inclusive and accessible educational financing alternative that would not only benefit university students, but would also contribute to the growth of the country's GDP through the integration of a more qualified workforce.